Follow-up Care among Medicaid Patients with Schizophrenia treated with Antipsychotics in the Inpatient Setting - Amanda M. Farr; David M. Smith; Jacqueline A. Pesa; Zhun Cao (Journal of Health Economics and Outcomes Research)
**Background:** For patients with schizophrenia, the transition from inpatient hospitalization to outpatient care presents a challenge to providing continuous care. Lapses in care during this time period can result in poor clinical outcomes. To date, there is little information regarding the association between inpatient antipsychotic treatment and outpatient care.